Insights in diabetes: Molecular mechanisms-Protectin DX, an anti-inflammatory and a stimulator of inflammation resolution metabolite of docosahexaenoic acid, protects against the development of streptozotocin-induced type 1 and type 2 diabetes mellitus in male Swiss albino mice - Rengachar, Poorani; Polavarapu, Sailaja; Das, Undurti N. (Frontiers in Endocrinology, 2023)
Our previous studies revealed that certain endogenous low molecular weight lipids have potent anti-diabetic actions. Of all, arachidonic acid (AA) and its anti-inflammatory metabolite lipoxin A4 (LXA4) are the most potent anti-diabetic molecules. Similar anti-diabetic action is also shown by resolvins. In our efforts to identify other similar lipid based anti-diabetic molecules, we investigated potential anti-diabetic action of protectin DX that also has anti-inflammatory actions like LXA4. Protectin DX {10(S),17(S)-dihydroxy-4Z,7Z,11E,13Z,15E,19Z-docosahexaenoic acid, also called as 10(S),17(S)-DiHDoHE)} prevented the development of streptozotocin-induced type 1 and type 2 diabetes mellitus in Swiss male albino mice. Protectin DX showed potent anti-inflammatory, antioxidant and anti-apoptotic actions that could explain its anti-diabetic action. In view of these beneficial actions, efforts need to be developed to exploit PDX and other similar compounds as potential anti-diabetic molecule in humans.